Memories Are Made of This Book review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Pas de Deux: The Royal Ballet in Pictures. PALABRAS CLAVE: Bill Cooper, Dee Conway, Johan Persson, photographs
Oberon Books, 2007.